Modelling risk-weighted assets: Looking beyond stress tests - Josef Sveda; Jiri Panos; Vojtech Siuda (Graduate Institute of International and Development Studies, 2024)
We propose an improved methodology for modelling potential scenario paths of banks' riskweighted assets, which drive the denominator of capital adequacy ratios. Our approach centres on modelling the internal risk structure of bank portfolios and thus aims to provide more accurate estimations than the common portfolio level approaches used in top-down stress testing frameworks. This should reduce the likelihood of significant misestimation of riskweighted assets, which can lead to unjustifiably high or low solvency measures and induce false perceptions about banks' financial health. The proposed methodology is easy to replicate and suitable for various applications, including stress testing and calibration of macroprudential tools. After the methodology is introduced, we show how our proposed approach compares favourably to the methods typically used. Subsequently, we use our approach to estimate the potential increase in risk weights due to a cyclical deterioration in credit parameters and the corresponding setup of the countercyclical capital buffer for the Czech banking sector. Finally, an illustrative, hands-on example is provided in the Appendix.
Keywords: E58; G21; G28; G29; 330; Risk weighted exposure; stress-testing; credit portfolio structure; countercyclical capital buffer